Phase II study of cabozantinib in patients with progressive glioblastoma: subset analysis of patients naive to antiangiogenic therapy. Issue 2 (14th August 2017) - Wen, Patrick Y; Drappatz, Jan; de Groot, John; Prados, Michael D; Reardon, David A; Schiff, David; Chamberlain, Marc; Mikkelsen, Tom; Desjardins, Annick; Holland, Jaymes; Ping, Jerry; Weitzman, Ron; et al.
Abstract: Background: Cabozantinib is a tyrosine kinase inhibitor with activity against vascular endothelial growth factor receptor 2 (VEGFR2) and MET that has demonstrated clinical activity in advanced solid tumors. This open-label, phase II trial evaluated cabozantinib in patients with recurrent or refractory glioblastoma (GBM). Methods: Patients were initially enrolled at a starting dose of 140 mg/day, but the starting dose was amended to 100 mg/day because of toxicity. Treatment continued until disease progression or unacceptable toxicity. The primary endpoint was objective response rate assessed by an independent radiology facility using modified Response Assessment in Neuro-Oncology criteria. Additional endpoints included duration of response, 6-month and median progression-free survival, overall survival, and safety. Results: Among 152 patients naive to prior antiangiogenic therapy, the objective response rate was 17.6% and 14.5% in the 140 mg/day and 100 mg/day groups, respectively, which did not meet the predefined statistical target for success. The proportions of patients alive and progression free at 6 months were 22.3% and 27.8%, respectively. Median progression-free survival was 3.7 months in both groups, and median overall survival was 7.7 months and 10.4 months, respectively. The incidence of grade 3/4 adverse events (AEs) was 79.4% and 84.7% in the 140 mg/day and 100 mg/day groups, respectively, and dose reductions due to AEs were experienced by 61.8% and 72.0%, respectively. Common grade 3/4 AEs included fatigue, diarrhea, and palmar-plantar erythrodysesthesia syndrome. Conclusions: Cabozantinib showed evidence of clinical activity in patients with recurrent GBM naive to antiangiogenic therapy, although the predefined statistical target for success was not met. At the starting doses assessed, AEs were frequently managed with dose reductions. Clinical Trials Registration Number: NCT00704288 (https://www.clinicaltrials.gov/ct2/show/NCT00704288 )